PERAN AUDIT INTERNAL DALAM MENINGKATKAN TATA KELOLA PERUSAHAAN - Padang, Novi Natalia (Jurnal Riset Akuntansi & Keuangan, 2023)
In the global economy, internal audit is established as an important tool for the proper management of any resource business economy. The main objective of this study is to determine the theoretical level of contribution of internal audit to corporate governance. Furthermore, this study also aims to examine the interaction between various factors of corporate governance, such as the board of directors, audit committee and external auditors, and the internal audit process. The results of this study indicate that internal audit plays an important role in effective corporate governance.